Heterogeneous Beliefs And Momentum Profits - Kankare, Jannika (My University, 2017)
The momentum phenomenon is one of the most well documented anomalies in financial research. However, the driving forces behind the anomaly have yet to be indisputably recognized. The purpose of this Master’s thesis is to investigate whether return continuation is derived from a situation where investors have heterogeneous beliefs or receive heterogeneous information. The dispersion of analysts’ earnings forecasts is used as a proxy for heterogeneity of beliefs concerning a firm’s fundamentals. The basic methodology is adopted from Verardo (2009). The contribution of this study to prior research is to examine the relationship between momentum profits and heterogeneous beliefs in different states of the market. This method allows for a closer investigation of the state-dependent properties of the phenomenon. The research period ranges from 2002 to 2015 and is divided into three separate sub-samples according to the prevailing market state: pre-crisis, crisis and post-crisis periods. The research data consists of monthly stock returns of S&P 500 survivor stocks. The main independent variable, dispersion (DISP), is the coefficient of variation of analyst forecasts of earnings for the end of the current or the next fiscal year. The purpose of the study is to provide an empirical link between momentum profits and heterogeneous beliefs using the dispersion of analysts’ forecasts as the main variable to measure the relation between the diffusion of forecasts per given stock and return continuation in a portfolio setting and in a time-series regression framework. The results from portfolio analysis are further tested with multivariate time-series regressions featuring the Fama-French three-factor model to assess whether covariance with possible risk factors has an impact on momentum returns. The findings of this study confirm only partially those of previous research papers. The portfolio analysis results suggest that the momentum-dispersion strategy works only during a “normal” state of the market. During a crisis period, the strategy is unable to yield positive returns and the profitability pattern is reversed in the aftermath of a momentum crash.
Keywords: Momentum; heterogeneous beliefs; behavioral finance; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|